Medium-Sized Towns: Methodological Approach, Functions and Productive Structure - Pasciaroni, Carolina (2012)
In recent years, scientific literature and spatial planning strategies have seen a renewed interest in so-called medium-sized cities. The prominence these cities have attained is primarily based on their potential to promote rural and regional development, reduce poverty and mitigate migration to large cities. Thus, their definition is not limited to population size but incorporates perspectives relating to the functions they perform within the territory. The aim of this study is to contribute to the conceptualisation of the analytical category of the medium-sized city and to its identification within the urban structure. The Province of Buenos Aires, Argentina’s main economic and population centre, has been selected as the region of study for this purpose.